ANALISIS KEMAMPUAN LITERASI NUMERASI DALAM MENYELESAIKAN SOAL PROGRAMME FOR INTERNATIONAL STUDENT ASSESSMENT (PISA) - Reflina Reflina; Fatma Liana Rahma P (Jurnal Karya Pendidikan Matematika, 2023)
This study aims to reveal deeper numeracy literacy skills in solving the Program for International Student Assessment (PISA) questions. This research was conducted at SMAS Cerdas Murni Tembung in the odd semester of the 2022/2023 academic year. The research subjects consisted of 28 students of class X MIPA-1. The research uses qualitative methods with a descriptive approach. The research instruments used were PISA test questions and interviews. The results showed that 44% of student were able to fulfill the ability indicators in using syimbols, numbers, and calculate mathematical operations contained in questions at levels 1, 4, and 5. In the indicator of the ability to analyze information from tables, graphs, diagrams, schematics, etc., it was obtained that 57,1% of students were able to solve PISA level 3. As well as indicators of skills in applying concepts as well as making decisions contained in level 2 and level 6 questions, 42,3% of students were able to meet these indicators. So that, the overall numeracy literacy ability of class X MIPA-1 students can be categorized as lacking in solving the Program For International Student Assessment (PISA) questions.